Hodnocení finanční výkonnosti společnosti prostřednictvím benchmarkingu - Vaněček, Martin (Vysoké učení technické v Brně. Fakulta podnikatelská, 2016)
Diplomová práce se zabývá tématem benchmarkingu jako součásti strategického řízení podniku v oblasti finanční výkonnosti. Cílem práce je prostřednictvím benchmarkingu zhodnotit relativní finanční výkonnost společnosti MESIT foundry, a.s. Teoretická část popisuje základní východiska strategického řízení a výkonnosti podniku, přičemž hlavní pozornost je věnována benchmarkingu a finanční analýze. Obsahem praktické části je prezentace výsledků a hodnocení benchmarkingové studie, zaměřené na porovnání výsledků finanční výkonnosti sledované společnosti MESIT foundry, a.s. s konkurencí čtyř velikostně srovnatelných firem v odvětví Výroba odlitků z lehkých neželezných kovů. Z časového hlediska je studie vymezena periodou let 2010 až 2014. Výsledky studie ukazují, že stabilně velmi dobrou úroveň relativní finanční výkonnosti dosahovala společnost MESIT foundry, a.s. v základních ukazatelích finanční analýzy, ve dvou provozních ukazatelích a v jednom ukazateli rentability. Negativním zjištěním je propad relativní finanční výkonnosti v roce 2014 u všech ukazatelů rentability s výjimkou ukazatele Rentability tržeb. Na základě získaných poznatků jsou v závěru představena doporučení ke zlepšení finanční výkonnosti analyzované společnosti.

This master´s thesis deals with the topic of benchmarking as part of a strategic procedure in the area of financial management performance. The goal of this thesis is to evaluate relative to benchmarking the financial performance of the company MESIT foundry, Inc. The theoretical part describes the basic assumptions of strategic controls and the company (business) performance, the main focus is devoted to benchmarking and financial analysis. The practical part contains a presentation of results and the evaluation of a benchmarking study focused on comparing the results of the financial performance of the monitored company MESIT foundry, Inc. to its competition of four companies which are comparable in size in the industry of Castings production from light nonferrous metals. This thesis covers the time period from 2010 to 2014. The study results show that the company MESIT foundry, Inc. has a consistently very good level of relative financial performance under the basic indicators of financial analysis, two are in the operating indicators and one indicator is of profitability. A negative finding is the decline in relative financial performance in 2014, all by profitability indicators with the exception of the indicator of return on sales. The recommendations for improvement of the financial performance of the analyzed company based on the obtained findings are presented at the end of this thesis.
Evaluation of the Company´s Financial Performance Using Benchmarkingu Approach
Keywords: benchmarking; výkonnost firmy; strategické řízení; finanční analýza; MESIT foundry; a.s.; Benchmarking; company performance; strategic management; financial analysis; MESIT foundry; Inc.